2021
DOI: 10.20452/pamw.16010
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis and inflammatory cardiomyopathy in 2021 – an update

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…On the other hand, the infectious factor (mainly viruses) is the most often raised reason for the occurrence of myocarditis [ 3 , 15 ]. In our study, the highest incidence of myocarditis in males was observed from November to April when the impact of infectious etiology of myocarditis might be especially expected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the infectious factor (mainly viruses) is the most often raised reason for the occurrence of myocarditis [ 3 , 15 ]. In our study, the highest incidence of myocarditis in males was observed from November to April when the impact of infectious etiology of myocarditis might be especially expected.…”
Section: Discussionmentioning
confidence: 99%
“…Myocarditis in children has become an increasingly significant condition over the years. Myocarditis can take various forms, from a mild subclinical course to fulminant acute myocarditis, entailing acute heart failure and being the cause of sudden cardiac death in 4–6% of cases [ 1 , 2 , 3 ]. In addition, a number of major complications have been observed, such as dilated cardiomyopathy or clinically significant arrhythmias [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myocarditis is defined as an inflammatory heart disease and is an important cause of dilated cardiomyopathy, acute heart failure, life-threatening arrythmias and sudden death [1][2][3][4][5]. It is estimated to affect thousands of adults and children around the world each year generating serious medical and social problems.…”
Section: Background and Rationalementioning
confidence: 99%